Efficient fault-tolerant implementations of non-Clifford gates with reconfigurable atom arrays - Yifei Wang; Yixu Wang; Yu-An Chen; Wenjun Zhang; Tao Zhang; Jiazhong Hu; Wenlan Chen; Yingfei Gu; Zi-Wen Liu (npj Quantum Information)
Abstract To achieve scalable universal quantum computing, we need to implement a universal set of logical gates fault-tolerantly, for which the main difficulty lies with non-Clifford gates. We demonstrate that several characteristic features of the reconfigurable atom array platform are inherently well-suited for addressing this key challenge, potentially leading to significant advantages in fidelity and efficiency. Specifically, we consider a series of different strategies, including magic state distillation, concatenated code array, and fault-tolerant logical multi-controlled-Z gates, leveraging key platform features such as nonlocal connectivity, parallel gate action, collective mobility, and native multi-controlled-Z gates. Our analysis provides valuable insights into the efficient experimental realization of logical gates, serving as a guide for the full-cycle demonstration of fault-tolerant quantum computation with reconfigurable atom arrays.